1995
DOI: 10.1111/j.1365-2958.1995.tb02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain fatty acids: the case for a novel form of cell‐cell signalling during Myxococcus xanthus development

Abstract: The esg locus is required for the formation of multicellular fruiting bodies and spores by the developmental bacterium Myxococcus xanthus. Studies have suggested that esg mutants are defective in the production of an essential signal (E-signal) used in cell-cell communication and that E-signalling is required for the expression of many developmental genes. Recently we have determined that the esg locus encodes components of a branched-chain keto acid dehydrogenase, a multienzyme complex involved in branched-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 0 publications
0
58
0
1
Order By: Relevance
“…The N-acyl homoserine lactones seem to be the most common molecules of this class, but other examples are known. It has been reported that fatty acids are among the set of signal molecules regulating differentiation in Myxococcus xanthus (Downard and Toal, 1995). The plant pathogen Ralstonia (formerly Pseudomonas) solanacearum uses a volatile signal molecule believed to be methyl hydroxypalmitate (Schell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The N-acyl homoserine lactones seem to be the most common molecules of this class, but other examples are known. It has been reported that fatty acids are among the set of signal molecules regulating differentiation in Myxococcus xanthus (Downard and Toal, 1995). The plant pathogen Ralstonia (formerly Pseudomonas) solanacearum uses a volatile signal molecule believed to be methyl hydroxypalmitate (Schell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the structure of the native E-signal has not been determined. Regardless of its structure, however, extracellular complementation by the endogenous E-signal requires cell-to-cell contact with the wild type (Downard and Toal, 1995;Dworkin, 1996), which contrasts with the volatile activity of 3-OH PAME.…”
Section: Discussionmentioning
confidence: 99%
“…E-signal is believed to be one or more short, branched-chain fatty acids, because the E-signal (esg ) locus appears to encode components of a dehydrogenase complex presumed to be involved in the synthesis of branched-chain fatty acids (Downard and Toal, 1995). In addition, defects in growth, pigmentation and development in esg mutants were corrected by the addition of several different short branched-chain fatty acids (Downard and Toal, 1995). Unfortunately, the structure of the native E-signal has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…xanthus development. Fruiting body formation and sporulation in Myxococcus bacteria is another example of controlled death aiding development (25,65,81). "Autocides," which include fatty acids as well as glucosamine, induce autolysis in dense cultures of Myxococcus xanthus and are required for normal fruiting body development and sporulation.…”
Section: Programmed Death In Bacterial Developmentmentioning
confidence: 99%